Bernard Shaw : The Darker Side - Silver, Arnold, 1927- (Stanford Stanford University Press, 1982)
Critical study of Bernard Shaw.
Include Pictures, Notes and Index
Keywords: Psychology -- Shaw, Bernard, 1856-1950